2022
DOI: 10.1007/s00424-022-02748-x
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of mitochondrial KCa3.1 channels in non-small cell lung cancer cells

Abstract: Lung cancer is one of the leading causes of cancer-related deaths worldwide. The Ca2+-activated K+ channel KCa3.1 contributes to the progression of non-small cell lung cancer (NSCLC). Recently, KCa3.1 channels were found in the inner membrane of mitochondria in different cancer cells. Mitochondria are the main sources for the generation of reactive oxygen species (ROS) that affect the progression of cancer cells. Here, we combined Western blotting, immunofluorescence, and fluorescent live-cell imaging to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 52 publications
3
8
1
Order By: Relevance
“…4). As shown previously ROS release rises in senicapoc-treated A549 cells after ~ 40 min ( uorescence increase compared to baseline values: control 22.9 ± 4.3% vs senicapoc 88.2 ± 25.4%) as shown previously (Bulk 2022). Following double treatment with erlotinib and senicapoc this occurs after 30 min (18.6 ± 4.9% control vs 102.3 ± 41.3% senicapoc and erlotinib; Fig.…”
Section: Senicapoc In Combination With Erlotinib Induces Ros Release ...supporting
confidence: 86%
“…4). As shown previously ROS release rises in senicapoc-treated A549 cells after ~ 40 min ( uorescence increase compared to baseline values: control 22.9 ± 4.3% vs senicapoc 88.2 ± 25.4%) as shown previously (Bulk 2022). Following double treatment with erlotinib and senicapoc this occurs after 30 min (18.6 ± 4.9% control vs 102.3 ± 41.3% senicapoc and erlotinib; Fig.…”
Section: Senicapoc In Combination With Erlotinib Induces Ros Release ...supporting
confidence: 86%
“…This overexpression is related to promalignant properties of the channel. Moreover, the studies [135,136] confirmed the localisation of the K Ca channels in the inner mitochondrial membrane in human colon and lung cancer cells. Likewise the Kv1.3 channels, inhibition of K Ca s (along with other anti-cancer drug administration) caused enhancement of apoptosis.…”
Section: Mitochondrial Potassium Channelsmentioning
confidence: 63%
“…The only member of the Calcium activated subfamily that has been shown to be expressed in NSCLC is KCa3.1 ( Bulk et al, 2015 ; 2017 ; 2022 ; Xu et al, 2021 ) ( Table 4 ). In particular, increased expression of the channel was detected in more aggressive cells ( Bulk et al, 2015 ) where it also regulates ICAM-1 dependent cell-cell adhesion between endothelial and cancer cells ( Bulk et al, 2017 ).…”
Section: Ion Channels In Human Cancermentioning
confidence: 99%